Development of a popular science book on the eco-wisdom of the Dayak Bakumpai Community - Nida Lessy; Muhammad Zaini; Suyidno Suyidno (HAFECS PRESS, 2026)
Local potential can be utilized effectively, for example by developing teaching materials based on local wisdom. By leveraging local potential, the learning process can gain experience based on real-world conditions in the area. Lepasan Village, located along the Barito River, has strategic potential as a learning resource with its rich flora and local wisdom that continues to be preserved from generation to generation by its people who come from the Dayak Bakumpai Tribe. This study aims to test the validity and practicality of the contents of the Popular Science Book (PSB) as a learning resource in the ethnobotany course. The research method used is development research with the education design research (EDR) model through Tessmer's formative evaluation. The research subjects involved 3 expert lecturers for expert review and 3 ULM Biology Education Master's students for individual evaluation. This study used validity sheet instruments and content practicality sheets. The results showed that the PSB was highly valid, with a score of 90.10%. Meanwhile, the practicality of the popular science book's content earned a score of 93.06, categorized as very good. Based on these test results, the PSB on local ecological wisdom of the Bakumpai Dayak community in Lepasan Village is procedurally suitable for use as supporting material for ethnobotany courses. These results encourage the integration of local wisdom in learning and support ecological conservation while providing contextual and meaningful learning resources for students, so that in the future, it is necessary to follow up with an effectiveness test on students' critical thinking skills on a wider scale. Abstrak. Potensi lokal dapat dimanfaatkan dengan baik salah satunya dengan mengembangkan bahan ajar yang berbasis pada kearifan lokal. Melalui pemanfaatan potensi lokal proses pembelajaran dapat memperoleh pengalaman berdasarkan keadaan nyata yang terdapat di daerah. Kelurahan Lepasan yang terletak di sepanjang Sungai Barito memiliki potensi strategis sebagai sumber belajar dengan kekayaan flora dan kearifan lokal yang terus dilestarikan secara turun-temurun oleh masyarakatnya yang berasal dari Suku Dayak Bakumpai. Penelitian ini bertujuan untuk menguji validitas dan kepraktisan isi Buku Ilmiah Populer (BIP) sebagai sumber belajar pada mata kuliah etnobotani. Metode penelitian yang digunakan yaitu penelitian pengembangan dengan model education design research (EDR) melalui evaluasi formatif Tessmer. Subjek penelitian melibatkan 3 dosen ahli untuk uji pakar (expert review) dan 3 mahasiswa Magister Pendidikan Biologi ULM untuk uji perorangan (one-to-one evaluation). Penelitian ini menggunakan instrument lembar validitas dan kepraktisan isi. Hasil penelitian menunjukkan validitas BIP dinyatakan sangat valid dengan skor 90,10%. Sedangkan kepraktisan isi buku ilmiah populer memperoleh skor 93,06 dengan kategori sangat baik. Berdasarkan hasil uji tersebut, PSB kearifan lokal ekologi masyarakat Dayak Bakumpai di Kelurahan Lepasan secara prosedural layak digunakan sebagai bahan pendukung mata kuliah etnobotani. Hasil ini mendorong integrasi kearifan lokal dalam pembelajaran dan mendukung pelestarian ekologi sekaligus menyediakan sumber belajar yang kontekstual dan bermakna bagi mahasiswa, sehingga kedepannya perlu ditindaklanjuti dengan uji efektivitas terhadap keterampilan berpikir kritis mahasiswa pada skala kelas yang lebih luas.